Substance Use and the Potential Impact on the Psychostimulant Response in Adult ADHD - Romero, Giovana (My University, 2024)
Background: Attention deficit and hyperactivity disorder (ADHD) is a neurodevelopmental disorder presenting with three core symptoms: inattention, hyperactivity, and impulsivity. The ADHD population is 3 times more susceptible to developing a cannabis use disorder compared to the general population. Psychostimulants are the first-line treatment for ADHD. There is currently no literature on the impact of cannabis on the psychostimulant response. Objectives: To compare the response to psychostimulant treatment in adults with ADHD between cannabis and non-cannabis users Methods: Sixty-five participants with a primary diagnosis of ADHD were recruited from the MacAnxiety Research Clinic and St. Joseph's Psychiatric Community Clinic. Participants were assigned to the cannabis, or non-cannabis group based on their cannabis status at baseline. The study was 8 weeks long and included 3 visits. The first visit of the study was called “Baseline” and would occur prior to the start of stimulant medication. Participants would be seen at two additional time points 4- and 8-weeks post-baseline visit at which point they would be taking their stimulant medication. At each study visit all participants would fill out the self-reported assessment battery conducted through REDCap. The study psychiatrist would assign a CGI-S score at the end of each visit and a CGI-I score at the end of week 4 and week 8. Results: Cannabis and non-cannabis users did not differ statistically in their BAARS-IV, CGI-S, and CGI-I scores over the study. Secondary outcomes investigating CUD, stimulant type, stimulant dosage, comorbidities, and responder rate did not produce significant outcomes. Conclusions: There was no difference in the treatment response to psychostimulants in adults with ADHD between cannabis and non-cannabis users. Further studies should continue exploring treatment response in populations with co-occurring adult ADHD and cannabis use.
Keywords: Cannabis; Substance Use Disorder; ADHD; Treatment